MORTALITY AND MORBIDITY PATTERN IN SMALL-FORGESTATIONAL AGE AND APPROPRIATE-FOR-GESTATIONAL AGE VERY PRETERM BABIES: A HOSPITAL BASED STUDY - Muhammad, Taj; Khattak, Asmat Ara; Rehman, Shafiq -ur- (Journal of Ayub Medical College Abbottabad, 2009)
Background: Very preterm babies are important group of paediatric babies who require special attention. These babies are known to have increased risk of morbidity and mortality. Studying the morbidity and mortality pattern for this important paediatric group can help in better understanding of their care in the hospital settings. Objective of the study was to compare the mortality and morbidity pattern in Small-for-gestational age and appropriate-for-gestational age very preterm babies. This hospital based prospective (cohort) study was conducted at the department of Paediatrics, Postgraduate Medical Institute, Lady Reading Hospital, Peshawar from March 2008 to April 2009. Methods: One hundred Small-for-gestational age (SGA) live born very preterm babies were compared with 100 appropriate-for-gestational age (AGA) very preterm babies having similar gestational ages. Information regarding gestational age, birth weight, mortality, and morbidity (in terms of various biochemical and clinical markers) were recorded on a pre-designed questionnaire. Data analysis was done using SPSS version 15. Results were interpreted in terms of descriptive (mean, proportions, standard deviation) and inferential statistical tests (with p-values). Results: There was no difference between the two groups (SGA Vs AGA) with regards to gestational age and gender of the babies The mean weight of SGA babies was significantly lower as compared to AGA babies (1.1±0.16 Kg Vs 1.5±0.2 Kg; p=0.001). As compared to AGA babies, the SGA babies had a higher mortality (40% Vs 22%, p=0.006), and higher morbidity in terms of hyperbilirubinaemia (67% Vs 51%, p=0.02) and hypocalcaemia (24% Vs 10%, p=0.02). The difference in the mortality between the two groups was more prominent in babies with gestational age ‰¤31 weeks (71.4% for SGA as compared to 39.3 % for AGA very preterm babies with gestational age ‰¤31 weeks). Conclusion: Very preterm SGA infants have significantly higher mortality and morbidity in comparison to the AGA babies. In deciding for therapeutic management of these babies, they need special attention in terms of factors as gestational age and the biochemical markers, to improve the outcome for these babies in the hospital settings. Keywords: Very preterm, SGA, AGA, mortality and morbidity